THE DYNAMICS OF DEPRESSION AMONG LATE ADOLESCENTS WITH AUTHORITARIAN PARENTING STYLES IN SAMARINDA - Rahma Ayu Aura; Andi Wahyu Irawan (Jurnal Konseling Pendidikan Islam, 2026)
The purpose of this study was to analyze factors contributing to depression among late adolescents (aged 18 to 24) in Samarinda City, with a focus on how authoritarian parenting styles shape their emotional experiences and cognitive distortions. Five participants with mild to moderate depressive symptoms (e.g., lack of interest, changes in sleep patterns, social withdrawal, and self-injurious behavior) were selected through purposive sampling to participate in this qualitative case study. Methods such as Person-Centered Therapy (PCT), Interpersonal Therapy (IPT), and Beck's cognitive theory framework were used to thematically analyze data collected from in-depth interviews and observations. Authoritarian parenting, family discord, and persistent academic pressure all contributed to participants' cognitive distortions, which manifested as pessimistic views of life and the future. Lack of motivation, decreased social functioning, repetitive thoughts, sleep disturbances, and feelings of worthlessness were all attributed to these conditions. Furthermore, low self-esteem and discrepancies in self-concept were influenced by a lack of emotional support from family. The study's findings suggest that multiple factors, including the interaction of cognitive, interpersonal, and family environmental factors, contribute to depression in late adolescence. Restructuring negative thought patterns, improving interpersonal relationships, enhancing self-acceptance, and enhancing psychological well-being in adolescents requires a multimodal intervention approach based on Cognitive Behavioral Therapy, Interpersonal Therapy, and Person-Centered Therapy for Individuals.